Effect of plantations on plant species diversity in the Darabkola, Mazandaran Province, North of Iran - HASSAN POURBABAEI; FATEMEH ASGARI; ALBERT REIF; ROYA ABEDI (Biodiversitas Journal of Biological Diversity, 2012)
Pourbabaei H, Asgari F, Reif A, Abedi R. 2012. Effect of plantations on plant species diversity in the Darabkola, Mazandaran Province, North of Iran. Biodiversitas 13: 72-78. In this study, the effect of plantations on plant species diversity was investigated in Darabkola, Mazandaran province, north of Iran. To conduct the study, a natural mixed forest, a broad–leaved plantation (Alnus subcordata-Acer velutinum) and a coniferous plantation (Cupressus sempervirens var. horizontalis-Pinus brutia) were selected. 35 sampling plots weretaken in systematic random method in each area. Data analysis was carried out using Simpson, Hill's N2, Shannon-Wiener and Mc Arthur's N1 diversity indices, Smith and Wilson evenness index and species richness. Results revealed that there were 32 plant species in natural forest and 30 plant species were found in each plantation. Rosaceae and Lamiaceae were the main families in the studied areas. Diversity and evenness indices of all vegetation layers had the most values in the natural forest. Richness of woody plants had the highest value in the natural forest, while herbaceous richness was the highest in coniferous plantation. Mc Arthur's N1 had the highest value among diversity indices and followed by Hill's N2, Shannon-Wiener and Simpson indices, respectively. In addition, results showed thatthere were significant differences among diversity, evenness and richness indices in all vegetation layers in the three studied areas.